Characteristics and outcomes of anti-mycobacterial therapy compared to no anti-mycobacterial therapy for NTM pulmonary disease. (June 2022) - Pennington, Kelly M.; Katta, Renuka; Weathered, Catherine; Pienaar, Elsje; Escalante, Patricio
Highlights: Fibronodular bronchiectatic NTM-PD treated with anti-mycobacterial therapy have a higher rate of sputum conversion. Patients not receiving anti-mycobacterial therapy were equally as likely to be asymptomatic at follow-up. Further studies are needed to clarify the impact of airway clearance regimens and evaluate longer-term follow-up.